From Structural Oppression to Social Liberation: A Progressive Reconstruction of the Exegesis of Surah al-Balad - Mutiullah; Subekti, Fiqi Restu (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2026)
Surah al-Balad is recognized as a seminal text in the struggle for the emancipation of the oppressed, resistance to oligarchic practices, and advocacy for the poor. This article examines the scarcity of progressive interpretations of al-Balad, which has confined the surah to ritual reading rather than a practical foundation for social advocacy. In response to the increasing complexity of contemporary social problems, the study aims to reconstruct al-Balad as a theological basis for contemporary social transformation. It employs historical description, hermeneutic analysis of the al-Balad text, and semiotic methods to uncover more authentic meanings. The findings indicate that al-Balad calls on believers to resist injustice and to establish a welfare-oriented social order; the text expresses divine condemnation of oligarchic actors characterized by greed and the subjugation of the vulnerable. The study concludes that the concentration of political and economic power in the hands of a few undermines social order and therefore compels adherents to take a firm stance through both the consolidation of faith and the improvement of their economic conditions. The article recommends raising believers’ critical awareness of their responsibility to support the economically disadvantaged and advancing efforts to create a more equitable economic system to achieve social welfare.